The Influence of Heuristic and Herding Behavior on Investment Decisions through Fomo on Retail Investors in Indonesia - Mery Oktori Uly Binu (Jurnal Indonesia Sosial Teknologi, 2024)
Retail investors in Indonesia are often influenced by psychological biases in making investment decisions. These biases, including heuristic and herding behaviors, often create a fear of missing out on key moments (FoMO) that impact investment decisions. This study aims to analyze the influence of heuristic behavior (representativeness bias, availability bias, anchoring bias) and herding behavior on investment decisions with FoMO mediation. The research used a survey method with 109 retail investor respondents and data analysis using smartPLS. The results show that herding behavior significantly affects FoMO, and FoMO also has a significant impact on investment decisions. In contrast, heuristic behavior has no significant influence on FoMO. These findings reinforce FoMO's role in the investment decision-making process among retail investors. Based on the results of data analysis from the hypothesis test, it can be concluded that heuristic behavior (representativeness bias, availability bias, and anchoring bias) does not affect the FoMO of retail investors in Indonesia. So any change in heuristic behavior (representativeness bias, availability bias, and anchoring bias) does not affect the FoMO of retail investors in Indonesia.